Comparatives between four varieties of rice (Oryza sativa L.) in some antioxidants content at flower stage: Comparatives between four varieties of rice (Oryza sativa L.) in some antioxidants content at flower stage - Guda, Muthik Abd Muslim; Ayoub, Aseel Fadel (Journal of Kerbala for Agricultural Sciences, 2018)
The purpose of this study is to identify and distinguish four varieties of rice (Oryza sativa L.) grown in Iraq, which are more resistant to stress and success in agriculture by using the measurement of some antioxidants content as a comparative guide to the success of varieties (amber 33, Jasmine, ferrite and black bean). The field study was conducted at the rice growing center in Mashkhab in Al-Najaf province in 2016. using RCBD in split plots arrangement with three replicates. The study included four varieties of rice (amber 33, jasmine, ferrite and black bean) at the flowering stage to measure total chlorophyll content, chlorophyll a, b, carotene ,proline , activity of Superoxide dismutase (SOD), Catalase (CAT) ,protease (pro) and total protein . The results showed an increase in total chlorophyll, chlorophyll a, b, and carotene, and the high activity of Superoxide dismutase (SOD) and catalase (CAT) in the black bean> amber33> jasmine, and finally the Ferrite cultivars respectively. The amount of Proline shows superiority of Amber 33 > jasmine >black bean > Ferrite, respectively. The protein did not show any significant differences between varieties. While Protease activity decreased in the black bean < amber33 < jasmine < Ferrite cultivars respectively. From the above results it can be used total chlorophyll content, chlorophyll a, b, carotene, proline and the activates of Superoxide dismutase (SOD) and Catalase (CAT) enzymes as indicators to select the most successful varieties in agriculture and to withstand stressful environmental conditions.